2022
DOI: 10.1101/2022.02.08.479621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiated kidney tubular cell-derived extracellular vesicles enhance maturation of tubuloids

Abstract: Advanced kidney in vitro models such as organoids or tubuloids still lack the intrinsic expression of various transport proteins needed for active secretory function. Extracellular vesicles (EVs), cell-derived structures that constitute the organ's microenvironment, are known to regulate various cellular processes, including kidney development and regeneration across the nephron. In this study, we propose a new application of renal tubular epithelial cell EVs as modulators for tubuloid functional maturation by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In vitro studies have demonstrated that proximal tubular EVs modify the activity of the epithelial sodium channel (ENaC) in the distal nephron [95], [96]. Similarly, EVs isolated from engineered proximal tubule cells were shown to improve the functional maturation of "tubuloids" (organoids showing a predominant tubular phenotype) including enhanced transport capacity of organic anion transporter 1 (OAT1) [97]. This raises the possibility that EVs mediate proximal-to-distal cross-talk to modify transport function (see Figure 4) [98].…”
Section: Evs In Tubular Function and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have demonstrated that proximal tubular EVs modify the activity of the epithelial sodium channel (ENaC) in the distal nephron [95], [96]. Similarly, EVs isolated from engineered proximal tubule cells were shown to improve the functional maturation of "tubuloids" (organoids showing a predominant tubular phenotype) including enhanced transport capacity of organic anion transporter 1 (OAT1) [97]. This raises the possibility that EVs mediate proximal-to-distal cross-talk to modify transport function (see Figure 4) [98].…”
Section: Evs In Tubular Function and Diseasementioning
confidence: 99%
“…110,111 Similarly, EVs isolated from engineered proximal tubule cells were shown to improve the functional maturation of “tubuloids” (organoids showing a predominant tubular phenotype) including enhanced transport capacity of organic anion transporter 1. 112 This raises the possibility that EVs mediate proximal-to-distal cross-talk to modify transport function (see Figure 5). 113 If confirmed in vivo , this would represent a novel layer of regulation in addition to other signaling systems.…”
Section: Evs In Tubular Function and Diseasementioning
confidence: 99%